2022
DOI: 10.3390/su14138088
|View full text |Cite
|
Sign up to set email alerts
|

Risk Aversion of B2C Cross-Border e-Commerce Supply Chain

Abstract: In recent years, with the booming development of the B2C cross-border e-commerce industry, the supply chain of B2C cross-border e-commerce faces many potential risk factors, which must be prevented. To solve this problem, this paper studies the supply chain risk factors of B2C cross-border e-commerce and puts forward avoidance strategies. First, the fitness network model of a dual local world is constructed by combining the fitness model with the local world model. Then, the fitness network model of the dual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In terms of supply chain risk propagation, the research results of infectious disease propagation dynamics models such as SIS and SIRS have been more prominent in recent years, and the results of several researches have also confirmed that the propagation dynamics model on the complex network can better reflect the law of risk propagation from the perspective of the supply chain as a whole [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 94%
“…In terms of supply chain risk propagation, the research results of infectious disease propagation dynamics models such as SIS and SIRS have been more prominent in recent years, and the results of several researches have also confirmed that the propagation dynamics model on the complex network can better reflect the law of risk propagation from the perspective of the supply chain as a whole [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Based on the susceptible-infected-removed (SIR) model, Li et al [28] developed a risk propagation model for supply chain risk management of agricultural goods. To simulate the risk propagation of the B2C cross-border e-commerce supply chain, Zhou et al [29] developed the SIRS virus propagation model and established the evaluation index system of supply chain risk immunity and external risk intensity in accordance with the supply chain risk immunity and external risk intensity. The elements that have the most effect on supply chain risk immunity and external risk intensity were determined using hierarchical analysis.…”
Section: The Complicated Network-based Sir Modelmentioning
confidence: 99%
“…Study [12] emphasizes, in general, the lower importance for e-commerce of political and regulatory risks compared to economic ones. At the same time, there is a higher level of sensitivity of internet companies of transboundary trade to the logistical risks associated with customs clearance, transportation, and distribution procedures.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%